Tradisi Maantaan Padi Setelah Walimatul ‘Ursy di Nagari Canduang Koto Laweh Kecamatan Canduang Kabupaten Agam Ditinjau dari Konsep Nafkah dalam Fiqih Munakahat - Gita Ramadana; Hamdani (Lembaga Yasin AlSys, 2026)
Although the maantaan padi tradition following walimatul ‘ursy is still practiced by the community of Nagari Canduang Koto Laweh, studies examining its implementation and status within the concept of maintenance under Islamic marital jurisprudence remain limited. This study aimed to analyze the implementation of the maantaan padi tradition following walimatul ‘ursy and to examine its status based on the concept of maintenance in Islamic marital jurisprudence. This study employed a qualitative approach through field research with a descriptive design. The informants comprised four individuals representing customary leaders, niniak mamak, Bundo Kanduang, and community members. Data were collected through interviews, observation, and documentation and were subsequently analyzed through data condensation, data presentation, and conclusion drawing and verification. The findings showed that the maantaan padi tradition was performed following walimatul ‘ursy by delivering three sacks of unhusked rice from the groom’s family to the bride’s family. The rice was carried in the dijujuang manner, presented through the basambah procession, and followed by a communal meal. The community interpreted the tradition as a symbol of kinship and the husband’s first provision of maintenance to his wife. From the perspective of the concept of maintenance in Islamic marital jurisprudence, the provision of three sacks of unhusked rice constitutes a customary symbol that does not replace the husband’s obligation to provide continuous maintenance. This study concludes that the maantaan padi tradition can represent the values of kinship and the husband’s responsibility, but its implementation does not eliminate the maintenance obligation established under Islamic law. These findings clarify the relationship between customary symbolism and maintenance obligations in Islamic family law practices within the Minangkabau community.